2017
DOI: 10.1371/journal.ppat.1006276
|View full text |Cite
|
Sign up to set email alerts
|

H1N1 influenza viruses varying widely in hemagglutinin stability transmit efficiently from swine to swine and to ferrets

Abstract: A pandemic-capable influenza virus requires a hemagglutinin (HA) surface glycoprotein that is immunologically unseen by most people and is capable of supporting replication and transmission in humans. HA stabilization has been linked to 2009 pH1N1 pandemic potential in humans and H5N1 airborne transmissibility in the ferret model. Swine have served as an intermediate host for zoonotic influenza viruses, yet the evolutionary pressure exerted by this host on HA stability was unknown. For over 70 contemporary swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 70 publications
9
57
0
Order By: Relevance
“…The H6 protein had a midpoint of thermal denaturation ( T m ) of 53.4 (Fig B). In comparison, the H1 HA of A/CA/04/09 has a T m of 57.9°C similar to that measured with whole human viruses and characteristic of an early 2009 pandemic human virus HA with fusion at pH 5.8 or lower (Fig C; Peacock et al , ; Russier et al , ). The H6 G225D protein had a midpoint of thermal denaturation ( T m ) of 50.5°C (Fig D), showing that the G225D mutation if anything slightly decreases stability (Linster et al , ; de Vries et al , ).…”
Section: Resultssupporting
confidence: 65%
“…The H6 protein had a midpoint of thermal denaturation ( T m ) of 53.4 (Fig B). In comparison, the H1 HA of A/CA/04/09 has a T m of 57.9°C similar to that measured with whole human viruses and characteristic of an early 2009 pandemic human virus HA with fusion at pH 5.8 or lower (Fig C; Peacock et al , ; Russier et al , ). The H6 G225D protein had a midpoint of thermal denaturation ( T m ) of 50.5°C (Fig D), showing that the G225D mutation if anything slightly decreases stability (Linster et al , ; de Vries et al , ).…”
Section: Resultssupporting
confidence: 65%
“…Further analysis of swine H1N1 viruses isolated after the 2009 pandemic revealed a shift in HA activation pH. Multiple post-2009 pandemic isolates had activation pH values that overlapped those of viruses that were adapted to humans, suggesting pigs as a bridging host for HA stabilization (64). In the current study, the lowest activation pH was observed for H1 viruses that were capable of sustained transmission in humans: Bris/59 (pH 5.3 to 5.4) and H1N1pdm09 viruses CA/07 and TX/15 (pH 5.4 to 5.5).…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for the lack of protection is attributable to the fusion stability of each HA. For example, viruses can escape the neutralization effects of HA stem-binding bnAbs by altering their HA composition such that more acidic conditions are necessary for fusion (33)(34)(35). Theoretical pI values of the HAs vs. measured EC50 values showed that H1/SI06 has the lowest pI as well as the most unfavorable compound neutralization capability (Fig.…”
Section: Resultsmentioning
confidence: 99%